Implementasi Pendidikan Multikultural dalam Pembelajaran Sejarah dengan Materi Islam pada Peserta Didik SMA Negeri 11 Medan - Daulay, Mawarda; Nababan, Surya Aymanda; Saragih, Ridho Gilang Amalsyah; Hutasuhut, Mei Sahputri (Medan Resource Center, 2023)
This study aims to explain the implementation of multicultural education in history lessons focusing on Islamic material for students at SMA Negeri 11 Medan. The research method used is qualitative with a case study approach. Information was collected through classroom observations, interviews with history teachers, and document analysis. The participants of the study were history teachers and eleventh-grade students at SMA Negeri 11 Medan. The results showed that the implementation of multicultural education in history lessons on Islamic material for students at SMA Negeri 11 Medan was carried out well. History teachers employed various approaches and strategies that consider the diversity of students. They explored diverse sources of Islamic history and used discussion methods, group assignments, and field activities to enhance students' understanding of Islamic history.